1979
DOI: 10.1136/pgmj.55.640.135
|View full text |Cite
|
Sign up to set email alerts
|

The human enteric coronaviruses

Abstract: SummaryA coronavirus was seen in the faeces from 15 (4-2%) of 355 adults with diarrhoea and from 5 (5-2%) of 96 adults without diarrhoea. Similar particles were seen in the faeces from 5 (2-2%) of 227 children aged 1-14 years with gastroenteritis, but in none of those from 230 infants under one year of age with gastroenteritis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

1982
1982
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 19 publications
1
22
0
Order By: Relevance
“…This observation is consistent with previous studies which have generally documented that coronavirus diarrhoea is usually mild ( Table 1). [12][13][14][15][16][17][18][19][20][21][22][23][24][25] Secondly, the median age of children with coronavirus infection (42 months) was significantly greater than in children with rotavirus infection (10 months), 7 which raises the possibility of age-dependent differences in susceptibility to infection, or perhaps different modes of virus transmission. Thirdly, the seasonality of coronavirus infection differed from that of rotavirus; rotavirus infection was most common between November and January whereas the highest monthly detection rates of coronavirus were between January and March.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This observation is consistent with previous studies which have generally documented that coronavirus diarrhoea is usually mild ( Table 1). [12][13][14][15][16][17][18][19][20][21][22][23][24][25] Secondly, the median age of children with coronavirus infection (42 months) was significantly greater than in children with rotavirus infection (10 months), 7 which raises the possibility of age-dependent differences in susceptibility to infection, or perhaps different modes of virus transmission. Thirdly, the seasonality of coronavirus infection differed from that of rotavirus; rotavirus infection was most common between November and January whereas the highest monthly detection rates of coronavirus were between January and March.…”
Section: Discussionmentioning
confidence: 99%
“…It is noteworthy that a study from a neighbouring country, Iran, reported that coronavirus ranked second (3%) to rotavirus as a cause of childhood viral gastro-enteritis. 25 However, while in some studies coronavirus has been associated with diarrhoea, 13,18,19,25 other studies have found coronavirus equally common in patients without diarrhoea. [15][16][17] Thus, the aetiological role of coronaviruses in human gastro-enteritis is not firmly established.…”
Section: Discussionmentioning
confidence: 99%
“…Coronaviruses and CVLPs are known to cause severe gastrointestinal illness in animals (Naqi et al, 1975;Horzinek and Osterhaus, 1979). Although many reports have appeared in the literature throughout the world identifying CVLPs as a possible etiologic agent of gastroenteritis in humans (Caul et al, 1975;Mathan et al, 1975;Baumeister et al, 1976;Maass et al, 1977;Moore et al, 1977;Rowland et al, 1978;Schnagl et al, 1978;Schnagl et al, 1979;Clarke et al, 1979;Maass and Baumeister, 1983;Gerna et al, 1985), CVLPs have also been identified in apparently healthy subjects (Mathan et al, 1975;Caul et al, 1975;Maass et al, 1977;Moore et al, 1977;Rowland et al, 1978;Schnagl et al, 1978;Schnagl et al, 1979;Clarke et al, 1979;Maass and Baumeister, 1983;Peigue et al, 1978;Weindling et al, 1980;Marshall et al, 1982;Puel et al, 1982;Sitbon, 1985). Although many reports have appeared in the literature throughout the world identifying CVLPs as a possible etiologic agent of gastroenteritis in humans (Caul et al, 1975;Mathan et al, 1975;Baumeister et al, 1976;Maass et al, 1977;Moore et al, 1977;Rowland et al, 1978;Schnagl et al, 1978;Schnagl et al, 1979;Clarke et a...…”
Section: Complement-like Lesionsmentioning
confidence: 99%
“…However, there is also direct evidence for involvement in enteric (e.g. strain HECoV 4408) (Zhang et al, 1994;Zhu et al, 2006) and suggestive evidence for involvement in neurological disease (Clarke et al, 1979;Flewett et al, 1987;Foley and Leutenegger, 2001;Gerna et al, 1985Gerna et al, , 1984Han et al, 2006;Jacomy et al, 2006;Luby et al, 1999;Resta et al, 1985;Saif, 2004;Schnagl et al, 1990Schnagl et al, , 1986Sitbon, 1985;Vabret et al, 2006;Zhu et al, 2006). HCoV are frequent causes of the common cold; usually a self-limiting upper respiratory tract (URT) illness (Heikkinen and Jarvinen, 2003).…”
Section: Introductionmentioning
confidence: 99%